If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying T + -9 = 24 + -10t Reorder the terms: -9 + T = 24 + -10t Solving -9 + T = 24 + -10t Solving for variable 'T'. Move all terms containing T to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + T = 24 + 9 + -10t Combine like terms: -9 + 9 = 0 0 + T = 24 + 9 + -10t T = 24 + 9 + -10t Combine like terms: 24 + 9 = 33 T = 33 + -10t Simplifying T = 33 + -10t
| 9x-1.5=2 | | X-2/7=1/9 | | 0.08-0.006= | | 18+5n+3n=54 | | 4x+x-7=1 | | 8p+9q-5(8p-3q+4r)= | | x+0.3x=8 | | -6-5+4x=-1 | | 3y+2x-3=6 | | 12x+3=x+36 | | 15/7=3x | | 30=5x+8y | | 2x-4.5=1.5 | | 9+9n=2n+2 | | 3x+2=8x+22 | | 35=5/9x | | 4x-5=3-1 | | 2(x-3)=4(3x+4) | | 5x-5[5-(7-5x)]= | | 6(x-3)=4(4x+3) | | 6v^2-9v-23=-8 | | 15x-12/3=16 | | 2(9x-3)+9=3(x+1)+x | | 8x-3[2-(6y-3)]= | | Y-7=0.25(x-5) | | 21t+4=-20 | | (2y)ex+x[(x^2)lny-1]dy=0 | | 3(2x-3)-7x=2-2(2+x) | | 3(2x+3)=16 | | 3-4[2-(6y-3)]= | | 2ydx+x[(x^2)lny-1]dy=0 | | 7y/10-8=9-5y/2 |